الدور الاقتصادي التنموي لتدوير المخلفات - الهرش, احمد فايز (University of Eloued جامعة الوادي, 2019)
ملخص: هدفت هذه الدراسة إلى بيان أهمية تدوير المخلفات كمورد اقتصادي جديد، بالإضافة لكونه طريقة فاعلة للتخلص الآمن من النفايات، ومعالجتها بكلف مالية وبيئيّة أقل. كما سعت الدراسة إلى تجلية أثر تدوير المخلفات على التنمية الاقتصادية ودورها في استدامة الموارد واستقصت الدراسة العوائد البيئية والاقتصادية لتدوير المخلفات بما يحقق النفع العام للدولة والمجتمع. الكلمات المفتاحية: التدوير؛ البيئة ؛ التنمية الاقتصادية ؛ المخلفات؛ الموارد. تصنيف JEL : Q50 ؛ Q20 . Abstract: This study aims to demonstrate the importance of recycling waste as a new economic resource, in addition to being an effective method for the safe disposal of waste and treat it at lower financial and environmental costs. The study also aimed to clarify the impact of waste recycling on economic development and its role in the sustainability of resources. The study explored the environmental and economic returns of waste recycling in order to benefit the public and the state. The study showed that the recycling of waste has positive economic and environmental effects, including the importance of recycling as an economic resource that maintains the sustainability of resources and finds resources at low costs compared to the original resource. Keywords: recycling; environment; economic development; waste; resources Jel Classification Codes: Q50, Q20.
مقال
Keywords: التدوير؛ البيئة ؛ التنمية الاقتصادية ؛ المخلفات؛ الموارد.